2014
DOI: 10.1111/sum.12138
|View full text |Cite
|
Sign up to set email alerts
|

The effect of peatland drainage and rewetting (ditch blocking) on extracellular enzyme activities and water chemistry

Abstract: Contact CEH NORA team at noraceh@ceh.ac.ukThe NERC and CEH trademarks and logos ('the Trademarks') are registered trademarks of NERC in the UK and other countries, and may not be used without the prior written consent of the Trademark owner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
0
9
1
Order By: Relevance
“…Changes in water table following blocking were variable but very small (<2 cm; Holden et al, ), but rewetting did lead to increases in wet‐indicator testate amoeba suggesting the creation of wetter conditions across the site (Swindles et al, ). However, there was no difference in extracellular enzyme activity in the year following ditch blocking (Peacock et al, ), and Francez, Gogo, and Josselin () noted a lag time in changes to microbial communities following restoration of a harvested raised bog. The lack of strong microbial or hydrological changes could be one reason for the associated lack of effect on DOM composition, as the water table was close to the bog surface despite the presence of open ditches (Holden et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in water table following blocking were variable but very small (<2 cm; Holden et al, ), but rewetting did lead to increases in wet‐indicator testate amoeba suggesting the creation of wetter conditions across the site (Swindles et al, ). However, there was no difference in extracellular enzyme activity in the year following ditch blocking (Peacock et al, ), and Francez, Gogo, and Josselin () noted a lag time in changes to microbial communities following restoration of a harvested raised bog. The lack of strong microbial or hydrological changes could be one reason for the associated lack of effect on DOM composition, as the water table was close to the bog surface despite the presence of open ditches (Holden et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Peat dams are also placed along the reprofiled ditches, creating shallow pools. The experimental site was used to investigate the effects of peatland rewetting on numerous ecological responses such as greenhouse gas emissions (Green et al, ), DOC fluxes (Evans et al, ), hydrology (Holden et al, ), vegetation (Green et al, ), extracellular enzyme activity (Peacock et al, ), and testate amoeba (Swindles et al, ). Further information concerning the study site can be found in Green et al () and includes soil physical and chemical properties, detailed meteorological data, and ditch topographical details.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, land management practises in these ecosystems often include draining to improve grazing capacity. This practise, leading to a long-term reduction in soil moisture, might provoke a substantial loss of soil C (Peacock et al 2014), as SOM decomposition is progressively stimulated by the changes in soil physical structure.…”
Section: Impacts On Soil Structure and Water Holding Capacitymentioning
confidence: 99%
“…Several studies demonstrated that blocking ditches increased the water table in the vicinity (e.g. Armstrong et al, 2010;Cooper et al, 2014;Peacock et al, 2015), although a comparison with an intact peatland in Northern England showed that water tables had not recovered to background levels even six years after blocking ditches (Holden et al, 2011). Water table recovery in blanket bogs is, however, usually small in magnitude, for example 2 cm (Wilson et al, 2010) or 9 cm (Worrall et al, 2007), whereas studies on boreal mires drained for forestry have found that blocking drainage ditches increased the water table in the vicinity by approximately 80 cm (Haapalehto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%